Exploring the Nature of New Radio Sources Identified in the ODIN Survey in the Vicinity of M42 (2025)
Recently, large radio surveys that search to map the neutral hydrogen distribution in our galaxy have led to the discovery and identification of new radio sources. This was the case of the THOR (The HI/OH/Recombination line survey of the Milky Way) survey, which produced a catalog of approx. 4400 sources between 1-2 GHz, and a reliable spectral index for approx. 1800 sources (Bihr et al., 2016). The follow-up to this survey was the ODIN (Orion Dynamics of Ionized and neutral gas) survey, this time studying M42 (Soler et al., 2019). ODIN then produced deep images of this region, allowing the identification and analysis of radio sources, most of which had not been catalogued and characterized. The present work is focused on the construction of a catalog that allows the study of radio sources located in the eastern region of M42, providing detailed information about their physical and morphological characteristics. For this, we used mapping and cross-matching techniques, where, through centralization and analysis of ODIN data, we were able to detect, collect, and classify these objects in a systematic way. In this specific case, we are dealing with sources that, although they emit strongly at radio wavelengths, may be invisible at other wavelengths. This catalog contains a total of 81 identified radio sources, of which 40 are sources that have never been catalogued and 41 have already been reported at least once. The findings indicate that for a subset of the identified radio sources, the main emission mechanism is synchrotron, with spectral indices ranging from α=-0.9 to α=-0.2. In terms of morphology, we rule out the possibility of them being supernova remnants (SNRs) since their angular sizes are very small. Of the 81 radio sources, six were particularly striking because they had two lobes, and in all cases, one of the lobes was more intense than the other, suggesting a possible relativistic beaming effect. This fact was later confirmed by calculating the inclination angle of the radio sources, which is in agreement with the values reported for radio galaxies. The morphological identification was confirmed by comparison with the NVSS survey, which also allowed us to verify their positions with a margin of error of no more than 6%, thus ruling out the possibility of false positives. Based on these results, we can affirm that these six sources are very possibly radio galaxies. This catalog may justify future deeper and higher resolution observations to determine the nature and evolutionary state of these possible radio galaxies through spectral index maps with high spatial resolution.